2018
DOI: 10.1155/2018/9520204
|View full text |Cite
|
Sign up to set email alerts
|

Hypospermia Improvement in Dogs Fed on a Nutraceutical Diet

Abstract: Male dog infertility may represent a serious concern in the canine breeding market. The aim of this clinical evaluation was to test the efficacy of a commercially available nutraceutical diet, enriched with Lepidium meyenii, Tribulus terrestris, L-carnitine, zinc, omega-3 (N-3) fatty acids, beta-carotene, vitamin E, and folic acid, in 28 male dogs suffering from infertility associated with hypospermia. All dogs received the diet over a period of 100 days. At the end of the evaluation period, no adverse effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…A similar trend was also observed for OTC serum concentration. We hypothesized that the alteration of reproductive functions, both in males and bitches, may be due to a state of chronic inflammation caused by the presence of harmful substances and contaminants (including OTC) within the body, which can be introduced by ordinary commercial pet food consumption [33][34][35]37]. Moreover, several studies showed the effects of antibiotics (tetracyclines, sulfa drugs, penicillins, aminoglycosides, and nitrofurans) and also heavy metals (cadmium, lead, and mercury) on the reproductive system, inducing estrous cycle disruption, impaired embryo implantation, impendent follicular development, breast and endometrial cancer, endometriosis, spontaneous abortions, sperm motility, and viability reduction [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar trend was also observed for OTC serum concentration. We hypothesized that the alteration of reproductive functions, both in males and bitches, may be due to a state of chronic inflammation caused by the presence of harmful substances and contaminants (including OTC) within the body, which can be introduced by ordinary commercial pet food consumption [33][34][35]37]. Moreover, several studies showed the effects of antibiotics (tetracyclines, sulfa drugs, penicillins, aminoglycosides, and nitrofurans) and also heavy metals (cadmium, lead, and mercury) on the reproductive system, inducing estrous cycle disruption, impaired embryo implantation, impendent follicular development, breast and endometrial cancer, endometriosis, spontaneous abortions, sperm motility, and viability reduction [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies showed the effects of antibiotics (tetracyclines, sulfa drugs, penicillins, aminoglycosides, and nitrofurans) and also heavy metals (cadmium, lead, and mercury) on the reproductive system, inducing estrous cycle disruption, impaired embryo implantation, impendent follicular development, breast and endometrial cancer, endometriosis, spontaneous abortions, sperm motility, and viability reduction [41][42][43][44][45][46]. It is also worth noting that previous in vitro evaluations highlighted the cytotoxic, proapoptotic, and proinflammatory effect of chicken bone treated with OTC according to appropriate withdrawal times [37,47,48] as well as the ability to induce DNA damages (activation of ATM and p53, phosphorylation of H2AX, and modifications of histone H3 methylation of lysine K4 in the chromatin) of the liquid form of OTC [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each collection, fresh semen samples were microscopically examined and evaluated after removing the gel clot. The spermatozoa activity was microscopically evaluated at 100x (to evaluate mass motility) and 400x (for individual motility) using a phase-contrast microscope (Micros Austria, Micros St. Veit Hunnenbrunn–Gewerbezone, Veit/Glan, Austria) [ 43 ]. A Neubauer hemocytometer was used to measure sperm concentration.…”
Section: Methodsmentioning
confidence: 99%
“…A work by Alonge et al showed that a commercial dry diet, including a complex of vitamin E (250 mg/kg), selenium (0.27 mg/kg), zinc (180 mg/kg), folic acid (1.5 mg/kg), and omega-3 polyunsaturated fatty acids (5 g/kg) increased the number of spermatozoa, and improved motility and membrane properties of the ejaculate in healthy normospermic dogs [ 148 ]. Moreover, dogs suffering from infertility were given a nutraceutical diet with balanced omega-6:omega-3 ratio (4:1), enriched with zinc (50 mg/kg), Lepidium meyenii (865 mg/kg), Tribulus terrestris (52 mg/kg), l -carnitine (420 mg/kg), beta-carotene (230 mg/kg), vitamin E (240 mg/kg), and folic acid (0.27 mg/kg), that increased motility percentage, semen volume and concentration, and the total number of sperms per ejaculation [ 149 ]. However, in both studies, the effects of zinc were not isolated.…”
Section: Role Of Zinc Status In the Occurrence Of Diseasementioning
confidence: 99%